Ultrasound assisted deep eutectic solvent based liquid phase microextraction for the preconcentration and spectrophotometric determination of amaranth (E123) in water and food samples. Issue 2 (4th March 2022) - Soylak, Mustafa; Baran, Sabri; Uzcan, Furkan
Abstract: A novel and easy environmental deep eutectic solvent based liquid phase microextraction method has been developed for the separation-preconcentration and spectrophotometric determination of amaranth. The deep eutectic solvent system is composed of tetrabutyl ammonium bromide (TBABr) and decanoic acid (DA). 300 µL of emulsifying agent tetrahydrofuran (THF) and 600 µL of deep eutectic solvent (DES) were employed. Quantitative recoveries were obtained at pH 5.0, sonication and centrifugation times of two minutes, and a model solution volume of 20 mL. The amaranth concentration was measured in a micro-cuvette spectrophotometer at 520 nm. The limit of detection (LOD), limit of quantification (LOQ), and preconcentration factor (PF) were 23 µg/L, 76 µg/L, and 33.3, respectively. The presented microextraction method has been validated by analyzing food and water samples by the method of standard addition.